A Comparative Study of Dispersion Techniques for Nanocomposite Made with Nanoclays and an Unsaturated Polyester Resin. (29th October 2011) - Bensadoun, Farida; Kchit, Nadir; Billotte, Catherine; Trochu, François; Ruiz, Edu
Abstract : Over the last few years, polymer/clay nanocomposites have been an area of intensive research due to their capacity to improve the properties of the polymer resin. These nanocharged polymers exhibit a complex rheological behavior due to their dispersed structure in the matrix. Thus, to gain fundamental understanding of nanocomposite dispersion, characterization of their internal structure and their rheological behavior is crucial. Such understanding is also key to determine the manufacturing conditions to produce these nanomaterials by liquid composite molding (LCM) process. This paper investigates the mix of nanoclays particles in an unsaturated polyester resin using three different dispersion techniques: manual mixing, sonication, and high shear mixing (HSM). This paper shows that the mixing method has a significant effect on the sample morphology. Rheology, scanning electron microscopy (SEM), and differential scanning calorimetry (DSC) characterization techniques were used to analyze the blends morphology and evaluate the nanoclays stacks/polymer matrix interaction. Several phenomena, such as shear thinning and premature polymer gelification, were notably observed.